St. Lucia : Technical Assistance Report-External Sector Statistics. (IMF Staff Country Reports; Country Report, 2022)
A remote technical assistance (TA) mission on external sector statistics (ESS) was conducted for the Central Statistical Office (CSO) of Saint Lucia during March 22-26, 2021. The mission was part of the Caribbean Regional Technical Assistance Centre (CARTAC) work program on External Sector Statistics (ESS).